Customer perspective towards service quality of telecommunication system; a study based on sri lanka telecom household customers in kandy district - Perera, R.A.S.A.; Piumali, W.M.H.; Herath, H.M.T.R. (University of Jaffna, 2016)
Telecommunication system of the country directly affect to the expansion of the market system in that particular country. Various types of telecommunication methods are used in this highly modern competitive world, in aim of making link with each other. In order to make it success, customers always draw their attention towards the quality of the service. Service Quality is one of the measurements to identify the customers' satisfaction which leads to retain the customers in an organization. Therefore identifying customer satisfaction based on service quality will help to get optimal future decisions. This study is carried out to address the main objective of, determine the relationship between the Service quality dimensions and the customer Satisfaction in telecommunication system in Sri Lanka. The sub objectives of this study are (1) to identify the most effective Service quality dimension in household telecommunication in Sri Lanka. (2)To identify the perceived gaps between customer expectations and perceptions of the Telecommunication service in Sri Lanka. This study is a Descriptive and Quantitative study. In order to obtain primary data questionnaire was used. SERVQUAL model used to identify the customers satisfaction related to its' five service quality determinants.100 household Sri Lanka Telecom customers in Kandy district are drawn for the sample, based on convenience sampling Method. Regression Analysis and Correlation Coefficients are used to analyze the data. Findings of the study highlight that SERVQUAL model dimensions positively effect to the customer satisfaction. The dimension Reliability is the mostly affected to the Customers Satisfaction on Telecommunication system in Sri Lanka. The dimension Empathy is the lowest effectual dimension towards customer satisfaction.
Keywords: Service quality; Servqual model; Telecommunicatio